Discovery and Validation of Circulating EVL mRNA as a Prognostic Biomarker in Pancreatic Cancer. (20th April 2021) - Du, Yan; Yao, Kai; Feng, Qingbo; Mao, Feiyu; Xin, Zechang; Xu, Peng; Yao, Jie
Abstract : Background . Circulating plasma mRNAs can be analyzed to identify putative cancer biomarkers. This study was conducted in an effort to detect plasma mRNA biomarkers capable of predicting pancreatic cancer (PACA) patient prognosis. Material and Methods . First, prognostic mRNAs that were differentially expressed in PACA in The Cancer Genome Atlas (TCGA) were established, after which microarray expression profiles from PACA patient plasma samples were utilized to specifically identify potential prognostic plasma mRNA biomarkers associated with this cancer type. In total, plasma samples were then collected from 79 PACA patients and 19 healthy controls to confirm differential mRNA expression via qPCR, while Kaplan–Meier analyses were used to examine the link between mRNA expression and patient overall survival. Results . In total, three prognostic differentially expressed genes were identified in PACA patient plasma samples, including SMAP2, PTPN6, and EVL (Ena/VASP-like). Plasma EVL levels were confirmed via qPCR to be correlated with tumor pathology p < 0.01, while the overall survival of patients with low plasma EVL levels was poor p < 0.01 . Multivariate Cox regression analyses further confirmed that plasma EVL levels were independent predictors of PACA patient prognosis. Conclusion . We found that PACA is associated with the downregulation of plasma EVL mRNA levels, indicating that this mRNA may be a viable biomarker associated with patient prognosis.